2014
DOI: 10.1016/j.geoderma.2014.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in water stable aggregate and soil carbon accumulation in a no-tillage with weed mulch management site after conversion from conventional management practices

Abstract: > We investigated at a site of no-tillage with weed mulch management (NWM). > Weed biomass, water stable aggregate (> 2 mm) and soil C increased with adopting NWM. > NWM increased soil C (60 g C m-2 yr-1) for 17 years, thus it is an effective method to sequester soil C. > C input as slashed weeds and litter were small (265-2317 g C m-2 yr-1) and corresponded to 2-11 % of C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…A previous study suggested that LF soil C was more sensitive to land use or environmental change than the heavy-fraction soil C [20]. During long-term abandonment, OM inputs and root activity increase AG + BG biomass, enhancing the formation of soil aggregates and the accumulation of soil C [9,21]. Significantly higher LF soil C and N in some soil layers in FF in our study suggest long-term OM accumulation.…”
Section: Plant-derived C and N In Forest Floor Litter And Abandoned Psupporting
confidence: 47%
“…A previous study suggested that LF soil C was more sensitive to land use or environmental change than the heavy-fraction soil C [20]. During long-term abandonment, OM inputs and root activity increase AG + BG biomass, enhancing the formation of soil aggregates and the accumulation of soil C [9,21]. Significantly higher LF soil C and N in some soil layers in FF in our study suggest long-term OM accumulation.…”
Section: Plant-derived C and N In Forest Floor Litter And Abandoned Psupporting
confidence: 47%
“…As the decomposition of both high and low quality OM (green tea and rooibos tea, respectively) was positively related to NT age, our results provide indirect evidence that the activity of both opportunistic bacteria and fungi increased with the time span since the conversion from CT to NT. Although our findings should be substantiated by further microbiological analyses, including microbial biomass and microbial community profiling, they are consistent with previous investigations and likely result from the lack of disruption of the hyphal network under NT [30,31] and the regular supply of C by cover crop, as well as the increase of soil aggregation over time under NT [32], which provides a variety of new habitats and micro-environments for soil microbial communities involved in the short-term processing of readily-decomposable organic C [12,33,34].…”
Section: Resultssupporting
confidence: 92%
“…This type of farming is highly based on productivity of the natural ecosystem, which is independent of agricultural industry products, and requires only sickles to cut weeds or to harvest (Kawaguchi and Toriyama, 2000) because farmers raise crops without tillage, chemical fertilizers, or other chemical inputs and do not remove weeds completely. Instead, weeds are used as soil cover based on the observation that weed cover mulching enhances carbon (Arai et al, 2014) and nutrient cycling (Komatsuzaki et al, 2012), contributing to improve crop growth. Therefore, this type of farming system is a more productive method for small-scale farmers in marginal environments because of lower labor and energy requirements and little dependence on external input into the system.…”
Section: Introductionmentioning
confidence: 99%
“…Altieri et al (1985) reported that compared with clean cultivation, soil covering by weeds and clover was effective on increasing numbers of ground predators (Carabidae, Staphylinidae, and spiders). Arai et al (2014) reported that carbon input into the soil from aboveground weed biomass and >2 mm increases in the water stable aggregate may be responsible for soil carbon sequestration by adopting NTW over a longer term. These results indicate that NTW systems could be a useful approach for increasing soil biological diversity and soil carbon sequestration after a long-term trial.…”
Section: Introductionmentioning
confidence: 99%